Case Report: Surgical Treatment for Intranasal Meningoencephalocele in a Cat - Nozue, Yuta; Yamazaki, Midori; Nakata, Kohei; Nakano, Yukiko; Yuki, Go; Kimata, Arata; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2020)
A 4-month-old cat with epileptic seizures and nasal discharge was presented, and diagnosed with intranasal meningoencephalocele based on the clinical symptoms and findings of CT and MRI. As liquorrhea was suspected, the meningoencephalocele was surgically excised and the postoperative course was favorable. For cribriform plate reconstruction, the autologous tunica vaginalis was used. Rhinorrhea of the cerebrospinal fluid and seizures disappeared after surgery. On CT and MRI at 7 months after surgery, septum formation between the cranial and nasal cavities was confirmed. Currently, no seizures have occurred even though no oral antiepileptic agent was administered. There are few reports of surgical treatment for meningoencephalitis, and there are no reports of reconstruction of the cribriform plate using tunica vaginalis, so we reported the details.